Predatory journals recruit fake editor - Sorokowski, Piotr; Kulczycki, Emanuel; Sorokowska, Agnieszka; Pisanski, Katarzyna (My University, 2017)
An investigation finds that dozens of academic titles offered ‘Dr Fraud’ — a sham, unqualified scientist — a place on their editorial board. Katarzyna Pisanski and colleagues report.
This article is freely available online at http://www.nature.com/news/predatory-journals-recruit-fake-editor-1.21662